2018
DOI: 10.1111/aji.13042
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol‐regulated innate antiviral responses of human endometrial stromal fibroblasts

Abstract: Problem: The contribution of fibroblasts to innate immune protection of the human female reproductive tract (FRT) against viral pathogens is relatively unknown. Method of Study: Endometrial (EM), endocervical (Cx), and ectocervical (ECx) fibroblasts were isolated from hysterectomy patients and grown in vitro. Fibroblasts were treated with the viral mimic poly (I:C) in the presence or absence of the sex hormone estradiol (E2), with gene expression measured by real-time RT-PCR and protein secretion by ELISA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…While primarily considered structural cells, they are key players in the innate immune response within the FRT (Wira et al, 2015). Fibroblasts express multiple PRRs, including TLR2, TLR3, TLR4, TLR5, TLR6, TLR9, RIG‐I, and MDA5, with endometrium fibroblasts generally expressing higher PRR levels than other sites in the FRT (Patel et al, 2018b; Patel Shen, & Wira, 2018). They mount innate immune responses against a broad range of incoming pathogens characterized by increased secretion of inflammatory cytokines and chemokines, leading to increased chemotaxis of immune cells (Patel et al, 2018b; Patel Shen, & Wira, 2018).…”
Section: Changes In Fibroblasts Induced By Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…While primarily considered structural cells, they are key players in the innate immune response within the FRT (Wira et al, 2015). Fibroblasts express multiple PRRs, including TLR2, TLR3, TLR4, TLR5, TLR6, TLR9, RIG‐I, and MDA5, with endometrium fibroblasts generally expressing higher PRR levels than other sites in the FRT (Patel et al, 2018b; Patel Shen, & Wira, 2018). They mount innate immune responses against a broad range of incoming pathogens characterized by increased secretion of inflammatory cytokines and chemokines, leading to increased chemotaxis of immune cells (Patel et al, 2018b; Patel Shen, & Wira, 2018).…”
Section: Changes In Fibroblasts Induced By Agingmentioning
confidence: 99%
“…Fibroblasts express multiple PRRs, including TLR2, TLR3, TLR4, TLR5, TLR6, TLR9, RIG‐I, and MDA5, with endometrium fibroblasts generally expressing higher PRR levels than other sites in the FRT (Patel et al, 2018b; Patel Shen, & Wira, 2018). They mount innate immune responses against a broad range of incoming pathogens characterized by increased secretion of inflammatory cytokines and chemokines, leading to increased chemotaxis of immune cells (Patel et al, 2018b; Patel Shen, & Wira, 2018). FRT fibroblasts secrete Type I and Type III interferons (IFNs) and thus induce an antiviral state in adjacent cells (Patel et al, 2018b; Patel Shen, & Wira, 2018).…”
Section: Changes In Fibroblasts Induced By Agingmentioning
confidence: 99%
“…Other genes in this population have also been associated with epithelial–stromal interactions, as well as innate immune responses, specifically M2 anti-inflammatory macrophage polarization ( PTPRS , PAQRF , PRDM1 , AXL and FOLR2 ) [ 32 , 33 , 34 , 35 ]. Similarly, in the ISG15+ population, most genes are involved in interferon signaling and innate immunity functions ( ISG15 , IF16 , MX1 , OAS1 , IF144L , OAS3 , OAS2, MX2, IFIT3 ) [ 36 , 37 ], suggestive of an activated stromal cell state/a subtype active in immunomodulation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, relevant future studies are needed to understand the role of hormones that regulated the menstrual cycle and the effect on sexual transmission of ZIKV in the FRT. Recently, it has been suggested that estradiol is associated with activation of the innate immune mechanism and initiation of the antiviral responses, and that the modulation by sexual hormones results in alteration of a woman's susceptibility to HIV-1 and other infections (61, 63). The understanding about the role of hormones in different stages of menstrual cycle or pregnancy may help to resolve question on the mechanism of ZIKV to persist in the FRT (Figure 2).…”
Section: Introductionmentioning
confidence: 99%